Heat in buildings data for digital compliance - McClelland, Joanne; Lewes, Aythan; Daillencourt, Louis; Smith, Sean (EALA Impacts CIC, 2024)
This report investigates the data that could be used to demonstrate compliance with a future Heat in Buildings Standard.
Keywords: buildings; heat; data; compliance; heat in buildings; heating; energy efficiency; property; dwelling; energy; EPC